Respiratory Viral Testing Rate Patterns in Young Children Attending Tertiary Care Across Western Australia: A Population-Based Birth Cohort Study - Taye, Belaynew; Sarna, Minda; Le, H.; Levy, A.; Minney-Smith, C.; Richmond, P.; Menzies, R.; Blyth, C.; Moore, Hannah (2024)
Background: An understanding of viral testing rates is crucial to accurately estimate the pathogen-specific hospitalisation burden. We aimed to estimate the patterns of testing for respiratory syncytial virus (RSV), influenza virus, parainfluenza virus (PIV) and human metapneumovirus (hMPV) by geographical location, age and time in children <5 years old in Western Australia. Methods: We conducted a population-based cohort study of children born between 1 January 2010 and 31 December 2021, utilising linked administrative data incorporating birth and death records, hospitalisations and respiratory viral surveillance testing records from state-wide public pathology data. We examined within-hospital testing rates using survival analysis techniques and identified independent predictors of testing using binary logistic regression. Results: Our dataset included 46,553 laboratory tests for RSV, influenza, PIV, or hMPV from 355,021 children (52.5% male). Testing rates declined in the metropolitan region over the study period (RSV testing in infants: from 242.11/1000 child-years in 2012 to 155.47/1000 child-years in 2018) and increased thereafter. Conversely, rates increased in non-metropolitan areas (e.g., RSV in Goldfields: from 364.92 in 2012 to 504.37/1000 child-years in 2021). The strongest predictors of testing were age <12 months (adjusted odds ratio [aOR] = 2.25, 95% CI 2.20–2.31), preterm birth (<32 weeks: aOR = 2.90, 95% CI 2.76–3.05) and remote residence (aOR = 0.77, 95% CI 0.73–0.81). Conclusion: These current testing rates highlight the potential underestimation of respiratory virus hospitalisations by routine surveillance and the need for estimation of the true burden of respiratory virus admissions.